International law reviewer - Cruz, Isagani A.; Cruz, Carlo L. (Quezon City : Central Book Supply Inc., 2024)
This volume incorporates essential references to recent important pronouncements, and events, in the field of International Law, which remains important to this day, and especially today.
1. General Principles -- 2. Sources of International Law -- 3. The international community -- 4. The united nations -- 5. The concept of the state -- 6. Recognition -- 7. The right existence and self-defence -- 8. The right independence -- 9. The right equality -- 10. Territory -- 11. Jurisdiction -- 12. The right legation -- 13. Consuls - 14. Treaties -- 15. nationality and statelessness -- 16. Treatment of aliens -- 17. Settlement of international disputes -- 18. War -- 19. Neutrality.
Keywords: INTERNATIONAL LAW -- EXAMINATIONS, QUESTIONS, ETC